2013
DOI: 10.1155/2013/841806
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cystectomy and Lymphadenectomy to Two Patients with Pelvic Kidney: Surgical Pitfalls and Considerations

Abstract: Our goal is to describe our experience in the difficulties encountered during radical cystectomy for muscle invasive bladder cancer in patients with contemporary pelvic kidney. Two patients with muscle invasive bladder cancer and contemporary pelvic kidney were subjected to radical cystectomy and extended lymphadenectomy with conversion to an ileal pouch. In both cases, lymphadenectomy was the first step after entering the true pelvis. In order to proceed to the cystoprostatectomy, careful dissection of the ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 7 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…Gülsün et al, 2000 [ 10 ], reported a right pelvic kidney supplied by three arteries arising from bilateral common iliac arteries and from ipsilateral internal iliac artery. Adamakis et al, 2012 [ 3 ], discovered two cases of left pelvic kidney during surgical staging of bladder carcinoma. In both cases, the left renal veins drained into IVC; the renal artery was single arising from distal part of aorta and left internal iliac artery, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gülsün et al, 2000 [ 10 ], reported a right pelvic kidney supplied by three arteries arising from bilateral common iliac arteries and from ipsilateral internal iliac artery. Adamakis et al, 2012 [ 3 ], discovered two cases of left pelvic kidney during surgical staging of bladder carcinoma. In both cases, the left renal veins drained into IVC; the renal artery was single arising from distal part of aorta and left internal iliac artery, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, the left renal veins drained into IVC; the renal artery was single arising from distal part of aorta and left internal iliac artery, respectively. Both studies presented a shorter length of ureter [ 3 ]. However the present case presented different features; that is, the arterial supply was from three sources, that is, aorta, common iliac, and inferior vesical artery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common ectopy type is pelvic kidney, and its incidence rate varies between 1/2100 and 1/3000. 3 There is a tendency for kidney-stone formation and hydronephrosis in ectopic kidneys. 4 Congenital kidney-anomaly patients' kidneys may lose function due to urinary-system anomalies, and nephrectomy could be needed.…”
Section: Laparoscopic Nephrectomy In Patients Withmentioning
confidence: 99%